Co-location of the oxazolidinone resistance genes optrA and cfr on a multiresistance plasmid from Staphylococcus sciuri. (6th March 2016) - Li, Dexi; Wang, Yang; Schwarz, Stefan; Cai, Jiachang; Fan, Run; Li, Jun; Feßler, Andrea T.; Zhang, Rong; Wu, Congming; Shen, Jianzhong
Abstract: Objectives: To identify and characterize the oxazolidinone/phenicol resistance gene optrA in Staphylococcus isolates. Methods: Fifty porcine staphylococci with florfenicol MICs of ≥16 mg/L were screened by PCR for the presence of the optrA gene. Transferability of optrA was examined by transformation and conjugation. Functionality of this gene was confirmed by cloning and expression in a susceptible Staphylococcus host. The optrA -carrying plasmid was completely sequenced and analysed. Results: A single Staphylococcus sciuri was optrA positive. This isolate carried the optrA gene on the 60 563 bp multiresistance plasmid pWo28-3, which also harboured the resistance genes, cfr, fexA, aadD, ble and aacA-aphD . Plasmid pWo28-3 is composed of three regions (A, B and C). Region A, which harboured all resistance genes except optrA, showed ≥99.8% nucleotide sequence identity to the corresponding region of plasmids pJP1 and pJP1-like from Jeotgalicoccus pinnipedialis and Staphylococcus lentus, respectively. The optrA gene located in region B differed from the optrA gene of the Enterococcus faecalis plasmid pE349 by four nucleotide substitutions, which also resulted in amino acid substitutions. This optrA variant also conferred resistance to oxazolidinones and phenicols in staphylococci. The 28 genes in region C represent the plasmid backbone and were apparently acquired from staphylococci, enterococci and nosocomiicocci. Conclusions: This is the first report of the optrA gene in staphylococci and of the coexistence of optrA and cfr on the same plasmid. Dissemination of this plasmid will substantially limit the efficacy of oxazolidinones. Surveillance of optrA in staphylococci of both human and animal origin is urgently warranted.